O uso dos pronomes retos em função de complemento : uma abordagem funcional sobre o fenômeno da flutuação - Silva , Cícero José da (2019)
This research analyze the syntactic- discursive consequences on the fluctuation of personal pronouns in third person , he, she , it and they, related to the function they take into the phrase in position before the verb and after the verb, as a theoretical base, usage the principles prototypicide, variation and linguistics change.(HOPPER 1991). These last principle motivator of grammaticalization, from classical functional linguistics. It was analyzed data of Corpora Discourse & Grammatical. (D&G) from Natal City, transcribed of corpus, verbal interaction situation and corpus CLELP, corpus of written texts in verbal interaction into a virtual platform of learning in science course of language with emphasis in teaching of Portuguese Language (CLELP). Methodologically, combine qualitative and quantitative bias, under the analyzing of data collected, describing and interpreting into inductive manners. Identifying that the syntactic function prototypica of pronouns in study works as subject, position before the verb. In concomitance, verifying the position after the verb, taking this category in phrases, having too, syntactic function of verbal complement (ACCUSATIVE). Besides this, there is one verbal group in use by the users with the purpose to assist the demand between the pression of the discourse. In that way, this occurs into the modality of the oral language function. Emphatize, therefore, that the accusative function exercises by pronouns he, she, it and they does not eliminate the original function of the pronoun, this way, the from itself, has two functions, and does not eliminate the unstressed pronominal form, that continue to act as verbal complement, the two forms co-existingin the same function.